1986
DOI: 10.1111/j.1600-051x.1986.tb01416.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease in Down's syndrome: a review

Abstract: Cross-sectional as well as longitudinal studies indicate that the prevalence of periodontal disease in persons with Down's syndrome (DS) under the age of 30 years is extremely high. It is even noted in the deciduous dentition. The progression of the disease is rapid, especially in the younger age groups. Severe periodontal breakdown with horizontal bone loss is often present in the lower anteriors. The large amount of plaque and calculus alone cannot explain the severity of periodontal disease in DS persons. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
102
1
6

Year Published

1993
1993
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(111 citation statements)
references
References 55 publications
2
102
1
6
Order By: Relevance
“…Whilst the differences in placement of restorations could be attributed to the lower caries rate of people with DS, [38][39] one might have similarly expected evidence of more periodontal therapy and orthodontics given the higher incidence of these problems in this population. 25,[38][39][40][41] Clearly, there are other contributory factors relating to treatment provision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst the differences in placement of restorations could be attributed to the lower caries rate of people with DS, [38][39] one might have similarly expected evidence of more periodontal therapy and orthodontics given the higher incidence of these problems in this population. 25,[38][39][40][41] Clearly, there are other contributory factors relating to treatment provision.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23] However, a recent study demonstrated a better clinical status for adults with LD than the general population although they had fewer teeth indicating that treatment is more likely to involve extraction of teeth. 24 Whilst people with DS have an increased prevalence of periodontal disease compared with the general population and other people with learning disability, 25 a carefully planned prevention programme can reduce its impact. 26  Adults with Down Syndrome (DS) have particular oral health needs, requiring a supportive, empathic and well-informed dental team.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that in DS patients, the prevalence and severity of advanced periodontal disease are increased [9][10][11][12]. The periodontal disease associated with DS is attributed to both endogenous and exogenous factors [13].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, there was only moderate relationship between dental plaque and periodontal disease severity in DS individuals (Lopez-Perez et al, 2002). Thus, rapid and severe periodontal destruction in those DS individual affected could not be explained by poor oral hygiene alone (Reuland-Bosma & van Dijk, 1986). …”
Section: Dental Cariesmentioning
confidence: 99%
“…Recently, it has been shown that a different salivary environment of electrolytes and pH is manifested in DS children, leading to the lower reported caries rate (Davidovich et al, 2010) 3.2 Periodontal disease DS individuals usually present with poor oral hygiene and manifested as marginal gingival inflammation, acute and subacute necrotizing gingivitis, advanced chronic periodontitis, loss of attachment in form of gingival recession and increased pocket depth, alveolar bone loss, suppuration or even abscesses, furcation involvement in the molars, increased tooth mobility, and even loss of teeth (Shaw & Saxby, 1986) (Figures 5B & 6). DS individuals had a prevalence of 60 to 90% percent and increased severity of periodontal disease compared with normal age-matched controls and subjects with other mental disabilities of similar age (Cutress, 1971b;Orner, 1976;Barnett et al, 1986;Reuland-Bosma & van Dijk, 1986;, Modeer et al, 1990;Shapira et al, 1991;Ulseth et al, 1991;Desai, 1997;Gabre et al, 2001;Lopez-Perez et al, 2002;Sakellari et al, 2005;Cheng et al, 2007;Khocht et al, 2010). Obviously the severity of periodontal disease among DS individuals is milder in recent years' reports as better dental care have been employed to take care of them early in their life.…”
Section: Dental Cariesmentioning
confidence: 99%